Dynamics of international advertising : theoretical and practical perspectives - Mueller, Barbara, 1958- (Peter Lang Publishing, 2017)
This is a comprehensive text for upper-division undergraduate or graduate level courses dealing with International Advertising.
Keywords: reklama a propagace; mezinárodní marketing; advertising; international marketing; monografie; monographs